Evaluasi Kualitas Layanan Jaringan Wireless Di Jurusan Teknik Informatika Dan Komputer Fakultas Teknik Universitas Negeri Makassar - Sri Nurmulyani; Satria Gunawan Zain; Fathahillah Fathahillah (UNIVED Press, 2026)
This study aims to evaluate the quality of wireless network services in the Informatics and Computer Engineering Department, Makassar State University and analyze the evaluation results based on Quality of Service (QoS) parameters with reference to the TIPHON standard. This study uses an action research method with a repetitive cycle. Data were collected through direct measurements of QoS parameters such as throughput, packet loss, delay, and jitter at various access points in the department building. 2. Based on the data obtained, the average signal strength value (-65) with the category